Reducing substance abuse in patients receiving prescription opioids for chronic non-cancer pain: a quality improvement and patient safety study in a primary care setting - Abdelrahman Ahmed; Emmanuel Akintoye; Neelima Thati (Greater Baltimore Medical Center, 2019)
Background: Chronic non-cancer pain is a common cause of primary care physicians' office visits. Objective: To determine the impact of adopting screening and monitoring measures in primary care settings on the illicit substance use behavior of patients receiving opioid analgesic prescriptions. Methods: This was a retrospective analysis of data on patients who were prescribed opioid analgesics for chronic non-cancer pain between 2014 and 2017 Q1 (i.e., first quarter of 2017). Study participants were patients who sought medical care at our academic primary care clinic practice that is part of an internal medicine residency program. Participants were adults (>18 years) who were considered eligible for opioid analgesics for chronic non-cancer pain. Interventions: (1) Rolling out of the chronic non-cancer pain management policy to clinic staff; (2) pain medication contracts with patients; (3) random urine drug screen (UDS) testing performed on patients during their clinic visits; 4) a didactics curriculum for internal medicine residents to highlight the key elements in utilizing and interpreting UDS results; (5) adding alerts to the electronic medical record that notifies clinic staff of discrepancy between patients' prescribed medications and UDS findings, as well as for quick identification of patients who had violated a stipulation of the contract; (6) mandatory regular utilization of Michigan State's online prescription monitoring records; and (7) employment of an on-site behavioral specialist for patients with mental illness or at risk of drug abuse. Main outcomes and measures: The main endpoint was the percentage of illicit drug use detected per year. Results: A total of 8096 UDS samples were collected over the study period. Mean (SD) participant age was 52 (SD 12) and 51% were male. Urine samples which had at least one illicit substance constituted 41% of the samples in 2014 prior to intervention. We found a significant decrease in the percentage of illicit substances after initiation of the intervention to 37% in 2015, 19% in 2016, and 12% in 2017Q1 (p < 0.001). Conclusion: Adopting a system-wide screening and monitoring measures in a primary care setting can significantly reduce the amount of illicit drug use among patients receiving an opioid prescription for non-cancer pain. This has important implications for patient safety and the current opioid epidemic in the USA. Further studies are needed to evaluate similar interventions in other settings such as a pain clinic.